Eph-Ephrin Signaling Mediates Cross-Talk Within the Bone Microenvironment - Arthur, Agnieszka; Gronthos, Stan (Frontiers in Cell and Developmental Biology, 2021)
Skeletal integrity is maintained through the tightly regulated bone remodeling process that occurs continuously throughout postnatal life to replace old bone and to repair skeletal damage. This is maintained primarily through complex interactions between bone resorbing osteoclasts and bone forming osteoblasts and osteocytes. Other elements within the bone microenvironment comprised of stromal cells and hematopoietic/ immune cells also contribute to maintaining skeletal integrity. Disruption of the dynamic interactions between these diverse cellular systems can lead to poor bone health and an increased susceptibility to skeletal diseases including, but not limited to osteopenia, osteoporosis, osteoarthritis, osteomalacia, and major fractures. Recent reports have implicated a direct role for the Eph tyrosine kinase receptors and their ephrin ligands during bone development, homeostasis and skeletal repair. These membrane-bound molecules comprising of the A and B subclasses mediate contact-dependent signaling through both the Eph receptors, termed forward signaling, and through the ephrin ligands, referred to as reverse signaling. This review will focus on Eph/ ephrin cross-talk as mediators of hematopoietic and stromal cell communication, and how these interactions contribute to blood/ immune cell function and skeletal integrity during normal steady state or pathological conditions.